Immunohistochemical Detection of Hairy Cell Leukemia in Paraffin Sections Using a Highly Effective CD103 Rabbit Monoclonal Antibody. Issue 2 (August 2015) - Morgan, Elizabeth A.; Yu, Hongbo; Pinkus, Jack L.; Pinkus, Geraldine S.
Abstract : Detection of the integrin subunit CD103 is a useful diagnostic tool in the diagnosis of hairy cell leukemia (HCL). Currently, flow cytometric analysis (FC) and frozen section immunohistochemistry (IHC) represent the only available methods of detection. This study is the first to describe the successful use of a CD103 antibody to identify HCL and HCL-variant in paraffin sections of formalin- or Bouin solution– fixed specimens (n = 68) using an immunoperoxidase technique. In other B-cell lymphoproliferative disorders that morphologically may resemble HCL, including chronic lymphocytic leukemia/small lymphocytic lymphoma (n = 32), mantle cell lymphoma (n = 23), lymphoplasmacytic lymphoma (n = 27), follicular lymphoma (n = 7), and marginal zone lymphoma (n = 13), lymphoid cells are nonreactive for CD103. In HCL, the CD103 staining pattern is predominantly membranous with delineation of delicate cytoplasmic projections. This CD103 antibody is an extremely valuable addition to the IHC panel for the diagnosis of HCL, especially in cases lacking FC analysis.